Inter- and intra-annual variation in milk composition in Antarctic fur seals (Arctocephalus gazella) - John Arnould; Ian L Boyd (1995)
The inter- and intra-annual variation in milk composition in Antarctic fur seals (Arctocephalus gazella) was investigated over three consecutive lactation periods (1990-1992) at Bird Island, South Georgia, which included one period of low food availability. One hundred and ninety-two milk samples were collected from 154 individuals. The mean milk composition was 40.5% ± 0.5% lipid, 10.4% ± 0.2% protein, 44.8% ± 0.6% water, 0.133% ± 0.0059% carbohydrate, and 0.694% ± 0.125% ash. Lipids contributed most (> 70%) of the gross energy of the milk. Water content could be used to predict lipid (r² = 0.83) and protein (r² = 0.13) content, but it could be used to predict gross energy content with the greatest accuracy of all (r² = 0.97). Stage of lactation, maternal mass, and year of sampling accounted for 27% of the observed variability in gross energy content. Following the perinatal period, milk lipid and gross energy content increased throughout lactation in all years, whereas water content decreased. Protein content decreased throughout lactation in 1990 but increased in the following 2 yr. Milk lipid and protein content decreased by as much as 14% and 5%, respectively, during each 1-2-d lactation bout. Minor, though significant, variation was found between the composition of milk collected from different mammae within individuals. The changes in composition observed both within and between lactation periods, and the level of inter- and intraindividual variation, emphasize the need for extensive sampling in order to describe adequately milk composition in otariids.